Distinct stem cells subpopulations isolated from human adipose tissue exhibit different chondrogenic and osteogenic differentiation potential - Rada, Tommaso (2011)
Recently adipose tissue has become a research topic also for the searching for an alternative stem cells source to use in cell based therapies such as tissue engineer. In fact Adipose Stem Cells (ASCs) exhibit an important differentiation potential for several cell lineages such as chondrogenic, osteogenic, myogenic, adipogenic and endothelial cells. ASCs populations isolated using standard methodologies (i.e., based on their adherence ability) are very heterogeneous but very few studies have analysed this aspect. Consequently, several questions are still pending, as for example, on what regard the existence/ or not of distinct ASCs subpopulations. The present study is originally aimed at isolating selected ASCs subpopulations, and to analyse their behaviour towards the heterogeneous population regarding the expression of stem cell markers and also regarding their osteogenic and chondrogenic differentiation potential. Human Adipose derived Stem Cells (hASCs) subpopulations were isolated using immunomagnetic beads coated with several different antibodies (CD29, CD44, CD49d, CD73, CD90, CD 105, Stro-1 and p75) and were characterized by Real Time RT-PCR in order to assess the expression of mesenchymal stem cells markers (CD44, CD73, Stro-1, CD105 and CD90) as well as known markers of the chondrogenic (Sox 9, Collagen II) and osteogenic lineage (Osteopontin, Osteocalcin). The obtained results underline the complexity of the ASCs population demonstrating that it is composed of several subpopulations, which express different levels of ASCs markers and exhibit distinctive differentiation potentials. Furthermore, the results obtained clearly evidence of the advantages of using selected populations in cell-based therapies, such as bone and cartilage regenerative medicine approaches.